Estimation of Critical Limit of Zinc in Basmati (Cv B-370) Rice Grown on Soils of Jammu Region - and Ajay Pratap Rai, Enoch Spalbar, Asim Kumar Mondal (Journal of the Indian Society of Soil Science, 2017)
A study was conducted with 40 representative soils from two blocks of Jammu district (20 each) where basmati rice (Cv B-370) is grown widely to estimate the critical limit of zinc (Zn) in soils and plant for predicting its response to Zn application. The DTPA extractable Zn in soils of Bishna and R. S. Pura blocks ranged between 0.38 to 0.69 and 0.44 to 0.65 with an average of 0.57 and 0.56 mg kg-1, respectively. The Bray’s per cent yield of basmati rice ranged between 52.2 to 99.5 and 41.5 to 97.0 in two blocks, respectively. The graphical methods of Cate and Nelson indicated that the critical limit of Zn in soils of Bishna and R.S. Pura block were 0.60 and 0.57 mg kg-1, respectively and in plants were 14.4 and 18.2 mg kg-1, respectively.